Antimicrobial nitric oxide releasing surfaces based on S-nitroso-N-acetylpenicillamine impregnated polymers combined with submicron-textured surface topography. (31st May 2017) - Wo, Yaqi; Xu, Li-Chong; Li, Zi; Matzger, Adam J.; Meyerhoff, Mark E.; Siedlecki, Christopher A.
Abstract : SNAP-impregnated textured polymer films having up to 38 day NO-release were shown to have synergistic effects in inhibiting bacterial adhesion. Abstract : A novel dual functioning antimicrobial CarboSil 20 80A polymer material that combines physical topographical surface modification and nitric oxide (NO) release is prepared and evaluated for its efficacy in reducing bacterial adhesion in vitro . The new biomaterial is created via a soft lithography two-stage replication process to induce submicron textures on its surface, followed by solvent impregnation with the NO donor, S -nitroso- N -acetylpenicillamine (SNAP), to obtain long-term (up to 38 d) NO release. The NO releasing textured polymer surface is evaluated against four bacteria commonly known to cause infections in hospital settings and the results demonstrate that the combined strategy enables a synergistic effect on reducing the bacterial adhesion of Staphylococcus epidermidis and Pseudomonas aeruginosa bacteria.